Building Competitive Advantage through Innovation, Creativity, Product Quality - Silvia Hendrayanti; Vina Nurauliya (BASKARA : Journal of Business and Entrepreneurship, 2021)
In the increasingly fierce competition, a business must have a strong enough competitiveness to be able to continue to compete with other businesses, especially similar businesses. It is very important for a business to make strategic steps to be able to continue to compete with competitors. This study aims to determine the effect of innovation, creativity and product quality on competitive advantage at Vibar Catering in Gunungpati. The data collection method in this study used a questionnaire by distributing questionnaires to 110 respondents. The sample in this study was some visitors who bought food and beverage products at Vibar Catering. The data analysis method used multiple linear regression, normality test, multicollinearity test, heteroscedasticity test, hypothesis test: t test, f test, and coefficient of determination test (R2). The results of this research found that product innovation variable (X1) t-count 4.742 > t-table 1.6592 and significant probability 0.000 <0.05, so that partially there is a positive and significant effect between Product Innovation (X1) on Competitive Advantage (Y). Product Creativity (X2) has a t-count of 2.536 > t-table 1.6592 and a significant probability of 0.000 <0.05, so that partially there is a positive and significant effect between Product Creativity (X2) on Competitive Advantage (Y). Product Quality (X3) has t-count 2.982> t-table 1.6592 significant probability 0.000 <0.05, so that partially there is a positive and significant effect between Product Quality (X3) on Competitive Advantage (Y). Vibar Catering in Gunungpati, it is expected to improve Product Quality by providing reliable catering services in food and beverage products, because the Product Quality variable has the lowest regression coefficient among other variables. If product quality is improved, consumer confidence in the product will also increase.